Performance enhancement of cross-axis-wind-turbine: Design and CFD analysis of an omni-directional flow concentrator - Christopher Clement Rusli; Keen Kuan Kong; Shin Yee Khoo; Su Xian Long; Wen Tong Chong (Alexandria Engineering Journal)
Wind energy harvesting faces challenges in turbulent, low-speed, and variable wind conditions, particularly in urban or complex terrain environments. Cross-axis wind turbines (CAWTs) aim to combine advantages of horizontal-axis wind turbines (HAWTs) and vertical-axis wind turbines (VAWTs), but previous designs using flat plate deflectors show suboptimal performance due to insufficient vertical wind redirection and lack of omni-directional capabilities. This study introduces a novel omni-directional flow concentrator (ODFC) to enhance CAWT performance, addressing these limitations. The ODFC was designed and refined through computational fluid dynamics (CFD) simulations, investigating parameters such as layer number, diameter, deflection angle, and fin count. Results demonstrate that the ODFC redirects wind vertically at 67.17–76.33 % of initial speed, improving upon the flat plate deflector by 50.66 %. Prototype fabrication and experimental validation confirmed these findings. Through CFD analysis, the CAWT-ODFC showed performance improvement of 100 %, 150 %, and 12 % compared to CAWT-flat plate, VAWT, and HAWT, respectively. Preliminary CFD analysis of a scaled-up integrated CAWT-ODFC yielded a promising power coefficient of 0.50, indicating potential for efficient energy harvesting in full-scale applications. These findings demonstrate that the ODFC significantly enhances the CAWT performance in diverse settings and challenging wind conditions including urban and remote areas.